A method of simultaneously measuring particle shape parameter and aerodynamic size. (August 2016) - Ding, Lei; Zhang, JinBi; Zheng, HaiYang; Wang, YingPing; Fang, Li
Abstract: For the purpose of classification of airborne particles, this paper describes an experimental apparatus for simultaneously measuring shape characteristics and aerodynamic size at single particle level. The shape of a particle is indicated through near forward scattering light collected by 3 PMTs placed at 120-degree offset azimuthal angles and the aerodynamic diameter is obtained by time-of-flight that a particle takes to traverse double laser beams. Laboratory experiments are performed on sampled aerosol particles in spherical, cuboid and elongated shape, and preliminary results indicate that the experimental apparatus has a good capability of discriminating between spherical and irregular particles. A variance factor of scattered light related to shape of ambient airborne particles under different conditions are also presented, which can be modeled using lognormal probability density distribution. Combined with aerodynamic size information, these results suggest potential uses in environmental aerosol monitoring for characterizing constituents of particles. Highlights: Measure aerosol particle shape parameter and aerodynamic size simultaneously. Preliminarily illustrate capability of discriminating nonspherical particle shapes. Shape parameters of ambient aerosols show lognormal probability distribution.